Gamification for grammar improvement - Soto Veliz, Martin Sezeu (Machala: Universidad Técnica de Machala, 2024)
This research examines gamification as a method to improve English grammar among 5th-year students at Eloy Alfaro Basic Education School. Gamification integrates game elements into educational activities to enhance motivation, engagement, and learning effectiveness. It has emerged as an innovative approach to address persistent challenges in education, particularly in language learning. The study specifically addresses issues such as low grammar proficiency, lack of motivation, and the reliance on traditional teaching methods that often fail to engage students in dynamic and meaningful ways. Using a mixed-methods approach and an explanatory experimental design, the study involved 11 students aged 9 to 12. Data collection tools included pretests, posttests, interviews, and classroom observations. Key aspects evaluated were the students' use of basic verb tenses, prepositions at, in, on, and their cognitive understanding of grammatical rules. These areas were selected due to their fundamental importance in building a strong foundation in English grammar. The intervention consisted of two sessions featuring gamified activities, which incorporated elements such as competition dynamics, rewards, and collaborative work to teach verb tenses and prepositions interactively. Activities were carefully designed to balance educational objectives with entertainment, ensuring that students remained engaged while achieving learning goals.
Esta investigación examina la gamificación como un método para mejorar la gramática del inglés entre los estudiantes de quinto año de la Escuela de Educación Básica Eloy Alfaro. La gamificación integra elementos de juego en actividades educativas para aumentar la motivación, el compromiso y la efectividad del aprendizaje. Ha surgido como un enfoque innovador para abordar desafíos persistentes en la educación, especialmente en el aprendizaje de idiomas. El estudio aborda específicamente problemas como el bajo dominio de la gramática, la falta de motivación y la dependencia de métodos de enseñanza tradicionales que a menudo no logran involucrar a los estudiantes de manera dinámica y significativa. Utilizando un enfoque de métodos mixtos y un diseño experimental explicativo, la investigación involucró a 11 estudiantes de entre 9 y 12 años. Las herramientas de recolección de datos incluyeron pruebas previas y posteriores, entrevistas y observaciones en el aula. Los aspectos clave evaluados fueron el uso de tiempos verbales básicos, las preposiciones at, in, on y la comprensión cognitiva de las reglas gramaticales. Estas áreas fueron seleccionadas debido a su importancia fundamental en la construcción de una base sólida en la gramática del inglés. La intervención consistió en dos sesiones con actividades gamificadas, que incorporaron elementos como dinámicas de competencia, recompensas y trabajo colaborativo para enseñar tiempos verbales y preposiciones de manera interactiva. Las actividades fueron diseñadas cuidadosamente para equilibrar los objetivos educativos con el entretenimiento, asegurando que los estudiantes se mantuvieran comprometidos mientras alcanzaban sus metas de aprendizaje.
Keywords: GAMIFICATION; TEACHING; LEARNING; MOTIVATION